Active management of third stage of labour: a comparative study of intra-umbilical oxytocin versus intramuscular oxytocin - Gupta, Neerja; Athokpam, Manjushree (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Postpartum haemorrhage is a single major and leading cause of maternal morbidity and mortality, not only in the developing countries but also in developed countries. Every 4 minutes one woman dies from pregnancy or child birth related complications. The present study is to compare oxytocin used via intra-umbilical or intramuscular route in the active management of third stage of labour with respect to duration and amount of bleeding. Methods: Four hundred pregnant women at term of a singleton pregnancy with spontaneous onset of labour were included in the study and were randomly divided into 2 groups of 200 women each. Group 1, intra-umbilical oxytocin 10U diluted in 10ml of saline, and Group 2, intramuscular oxytocin 10U were given after the delivery of baby. Results: The outcome criteria with respect to third stage of labour were: duration of the 3rd stage of labour, blood loss by volume, difference in haemoglobin. A significant reduction in duration of third stage (p = 0.001) and blood loss in third stage (p =0.0001) in intra-umbilical oxytocin group was found when compared with intramuscular oxytocin use. Conclusions: Intra-umbilical oxytocin is better alternative to intramuscular oxytocin in active management of third stage of labour.